Tantangan Peran Notaris Dalam Proses Merger Konglomerat: PT Aplikasi Karya Anak Bangsa (Gojek) dan PT Tokopedia - Syarifah Shamira; Flora Dianti (PROGRAM STUDI MAGISTER HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO, 2025)
Merger is a corporate legal action that combines two or more companies into one entity to increase efficiency, and business diversification. This research focuses on the conglomerate merger between PT Aplikasi Karya Anak Bangsa (Gojek) and PT Tokopedia, which formed a holding company called GoTo Group. The purpose of this study is to analyze the role of notaries in the stages of a conglomerate merger of public companies in accordance with applicable laws and regulations, such as the Limited Liability Company Law (UUPT) and POJK No. 74/POJK.04/2016. The research method used is normative juridical with an analytical descriptive approach. The results show that notaries have an important role in every stage of the GoTo conglomerate merger, starting from the preparation of the Merger Deed, changes to the Articles of Association, to the submission of documents to the Ministry of Law and Human Rights through the Legal Entity Administration System (SABH). In addition, the notary also ensured that the merger did not violate the principles of fair business competition in accordance with Law Number 5 Year 1999, and protected the rights of minority shareholders, creditors, and employees.